(untitled) (Biological Sciences - PJSIR, 2024)
Rice is one of the primarily grown cereals in the universe and is eaten by 60% of the world population as a staple food. Three indigenous extra long grain rice varieties grown in Punjab, Pakistan were analyzed for their cooking, chemical and physical properties. A comparison of newly developed varieties was done with the existing Basmati 515, super Basmati. Among all studied traits, varieties differ considerably at P > 0.001 value for paddy yield, plant height, grain dimensions, elongation/expansion ratio, gel uniformity, temperature for gelatinization, alkaline spread value and aroma on sensory perception. The volume expansion ratio varied from 4.5 to 5.5. The highest volume expansion ratio was acquired for Kissan Basmati. Grain elongation after cooking ranged between 14.7 to 16.6 mm. The values for the amylose ranged between 22.50 to 24.0% and amylopectin ranged between 76-77.5%. The range of AGL of extra long grain ranged from 8.10 to 8.23 mm, L/B ratio from 4.47 to 5.47. All verified varieties showed resistance against BLS, blast and BLB incidence.